Mapping the Trends of Inquiry-Based Learning Research in Elementary Science Education: A Bibliometric Analysis - Awinda, Wina; Rohmani; Mahendra, Yasinta; Junaidi (Journal for Lesson and Learning Studies, 2024)
Inquiry-based learning in science education at the elementary level holds significant potential to enhance teaching quality, yet its developmental trends remain insufficiently mapped. This article aims to analyze the research trends of inquiry-based learning in elementary science education using a bibliometric approach. The study was conducted through four stages of analysis: identification, screening, eligibility, and inclusion. Data were retrieved from the Scopus database using the keywords “inquiry-based learning,” “science,” and “elementary school,” yielding 43 selected documents from 2014 to 2023, all in English. The analysis reveals three key terms that frequently appear in these studies: “inquiry-based learning” (22 occurrences, link strength 76), “students” (14 occurrences, link strength 76, links 35), and “elementary school” (7 occurrences, link strength 37). The highest number of publications was recorded in 2023 with eight documents, while the lowest numbers occurred in 2017 and 2021, with only one document each. The study concludes that inquiry-based learning approaches in elementary science education have received limited attention from international researchers. Thus, further studies are needed to expand the scope of this topic and enhance its contributions to primary education.